PENDAMPINGAN PENDIRIAN KOPERASI DESA MERAH PUTIH LEMBANG MA’KUANPARE BERBASIS PARTISIPASI - Lusdani, Westerini; Patadungan, Ellyn; Pagiu, Chrismesi; Marniati, Marniati; Pundissing, Rati (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Community-based economic development is a crucial strategy for achieving sustainable rural welfare. This community engagement program aims to assist the residents of Lembang Ma’kuanpare in establishing the Merah Putih Village Cooperative through a participatory approach and the utilization of local potential. The method used is Participatory Action Research (PAR), integrating the processes of needs assessment, training, planning, organizational formation, and legal registration of the cooperative. The results show that participatory cooperative development enhances community understanding and involvement, fosters local leadership, and creates new social institutions that support village economic development. The established cooperative functions not only as a platform for collective enterprise but also as a driving force for social transformation based on local potential.